2008
DOI: 10.1016/j.bbrc.2008.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Cell shape regulation by Gravin requires N-terminal membrane effector domains

Abstract: Gravin (AKAP12, SSeCKS) is a scaffolding protein that acts as a potent inhibitor of tumor metastasis in vivo and in vitro, and regulates morphogenesis during vertebrate gastrulation. Despite being implicated in many cellular processes, surprisingly little is known about the mechanism by which Gravin elicits cell shape changes. In this work we use in vitro cell spreading assays to demonstrate that the Gravin N-terminus containing the three MARCKS-like basic regions (BRs) is necessary and sufficient to regulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Overexpression of SSeCKS was reported to inhibit cellular migration and alter cytoskeletal organization and cell shape in several cultured cell types and to inhibit the growth of prostate tumor cells in nude mice [20–25]. Along similar lines, Weiser et al [26] recently reported that gravin regulates cell spreading in COS7 cells. A report by Lee et al [27] further suggests that SSeCKS expression in astrocytes may regulate endothelial permeability at the blood brain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of SSeCKS was reported to inhibit cellular migration and alter cytoskeletal organization and cell shape in several cultured cell types and to inhibit the growth of prostate tumor cells in nude mice [20–25]. Along similar lines, Weiser et al [26] recently reported that gravin regulates cell spreading in COS7 cells. A report by Lee et al [27] further suggests that SSeCKS expression in astrocytes may regulate endothelial permeability at the blood brain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mouse AKAP12 was identified independently as a phosphatidylserine-binding protein (16, 24), a function that maps to the effector domains and that facilitates association with plasma membranes and PKC (13). The three effector domains are required for AKAP12 to mediate cell flattening (25). …”
Section: Introductionmentioning
confidence: 99%
“…The non-canonical Wnts activate several downstream PCP effectors, including the small GTPase Rho, which mediates many of the effects of the PCP pathway during gastrulation (Habas et al, 2003;Marlow et al, 2002) by affecting cell polarity, cell shape changes and movement (Etienne-Manneville and Hall, 2002;Hall, 1998). Although most work on small G-proteins during gastrulation has focused on the role of non-canonical Wnts in controlling their activity (Habas et al, 2003), several other regulators of Rho are required for proper gastrulation, including the scaffolding protein Gravin (Akap12), which is essential for mesodermal cells to convert from amoeboid cell movement to intercalative cell behaviors at the end of gastrulation in order for extension to occur (Weiser et al, 2007;Weiser et al, 2008). RhoA activates the Formins, which control actin polymerization, and Rho-dependent kinase (Rock), which phosphorylates the regulatory light chain of non-muscle myosin (Mlc) (Etienne-Manneville and Hall, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cells were transfected as described (Weiser et al, 2008). Conditioned media were obtained by culturing L-cells or Wnt5a/L-cells in DMEM containing 10% FBS without selective antibiotics for 5 days.…”
Section: Mammalian Tissue Culturementioning
confidence: 99%